‘Autoflogulation’ – a word to help students to be precise in explaining blood flow control - Ming, Cheng Hwee (Journal of Physiological Society of Nepal, 2021)
I wish to share with my Physiology teaching colleagues a few common observations among students on the imprecise and loose way in which they sometime use key Physiology words.The term ‘autoregulation’ generally means the ability of the body to respond to challenges and changing circumstances and maintain normal essential parameters. This broad meaning similar to the term homeostasis can then be used in sentences like ‘plasma osmolarity is autoregulated or ‘plasma potassium concentration is autoregulated’.